Comparison of quantitative Y‐90 SPECT and non‐time‐of‐flight PET imaging in post‐therapy radioembolization of liver cancer. Issue 10 (30th September 2016) - Yue, Jianting; Mauxion, Thibault; Reyes, Diane K.; Lodge, Martin A.; Hobbs, Robert F.; Rong, Xing; Dong, Yinfeng; Herman, Joseph M.; Wahl, Richard L.; Geschwind, Jean‐François H.; Frey, Eric C.
Abstract : Purpose: Radioembolization with yttrium‐90 microspheres may be optimized with patient‐specific pretherapy treatment planning. Dose verification and validation of treatment planning methods require quantitative imaging of the post‐therapy distribution of yttrium‐90 (Y‐90). Methods for quantitative imaging of Y‐90 using both bremsstrahlung SPECT and PET have previously been described. The purpose of this study was to compare the two modalities quantitatively in humans. Methods: Calibration correction factors for both quantitative Y‐90 bremsstrahlung SPECT and a non‐time‐of‐flight PET system without compensation for prompt coincidences were developed by imaging three phantoms. The consistency of these calibration correction factors for the different phantoms was evaluated. Post‐therapy images from both modalities were obtained from 15 patients with hepatocellular carcinoma who underwent hepatic radioembolization using Y‐90 glass microspheres. Quantitative SPECT and PET images were rigidly registered and the total liver activities and activity distributions estimated for each modality were compared. The activity distributions were compared using profiles, voxel‐by‐voxel correlation and Bland–Altman analyses, and activity‐volume histograms. Results: The mean ± standard deviation of difference in the total activity in the liver between the two modalities was 0% ± 9% (range −21%–18%). Voxel‐by‐voxel comparisons showed a good agreement in regions corresponding roughly to treated tumor and treated normal liver; the agreement was poorer in regions with low or no expected activity, where PET appeared to overestimate the activity. The correlation coefficients between intrahepatic voxel pairs for the two modalities ranged from 0.86 to 0.94. Cumulative activity volume histograms were in good agreement. Conclusions: These data indicate that, with appropriate reconstruction methods and measured calibration correction factors, either Y‐90 SPECT/CT or Y‐90 PET/CT can be used for quantitative post‐therapy monitoring of Y‐90 activity distribution following hepatic radioembolization.